Pengaruh Aliran Sempalan Terhadap Pengajaran Agama di Desa Tanah Terban Kecamatan Karang Baru - Maulana Bagas Perkasa; Indra Harahap (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Talking about a "splinter movement" means starting from an understanding about "orthodoxy" or "mainstream"; because of movement A splinter is a movement that deviates from or separates itself from prevailing orthodoxy. The research results show that the splinter sect in Tanah Terban Village plays an important role in the dynamics of religious teaching in the village. Its presence brought significant changes in aspects of the curriculum, methods and religious teaching materials that were different from formal madrasas. This change has an impact on the village community's understanding of religion, triggering tensions between religious communities, and has the potential to cause social disintegration.